Physical Polyurethane Hydrogels via Charge Shielding through Acids or Salts. Issue 7 (31st January 2018) - Leiendecker, Mai‐Thi; Licht, Christopher J.; Borghs, Jannik; Mooney, David J.; Zimmermann, Marc; Böker, Alexander
Abstract: Physical hydrogels with tunable stress‐relaxation and excellent stress recovery are formed from anionic polyurethanes via addition of acids, monovalent salts, or divalent salts. Gel properties can be widely adjusted through pH, salt valence, salt concentration, and monomer composition. We propose and investigate a novel gelation mechanism based on a colloidal system interacting through charge repulsion and chrage shielding, allowing a broad use of the material, from acidic (pH 4–5.5) to pH‐neutral hydrogels with Young's moduli ranging from 10 to 140 kPa. Abstract : Stress‐relaxing physical hydrogels with excellent recovery behavior are formed in an unconventional gelation mechanism controlled through electrostatic repulsion and charge shielding. Both acidic and pH‐neutral hydrogels can be obtained by physically crosslinking anionic polyurethanes with either acids or salts, offering a nontoxic in situ gelation unlike conventional isocyanate‐based hydrogels derived from polyurethanes.